Crop and fallow contribution to N2O emissions of contrasting crop sequences - Gregorutti, Viviana Carolina; Novelli, Leonardo Esteban; Cuatrin, Alejandra; Benedit, Beltrán G.; Caviglia, Octavio (Elsevier, 2025)
Crop sequences (CS) in South America, characterized by a high proportion of soybean and a concerning soil nutrient mining, urgently require reconfiguration towards more sustainable cropping systems. New configurations of CS may impact nitrous oxide (N2O) emissions. Although reported reported at the CS level in a few studies, the specific contributions of each sequence component, such as fallow periods or crops, have rarely been thoroughly analyzed. The aims were: i) to quantify total N2O emission from different CS with contrasting cropping intensity in a long-term experiment that included all phases, ii) evaluate the drivers of N2O emission fluxes and iii) estimate the contribution of each component of the CS to total N2O emissions. The study was conducted combining crops of soybean (S), maize (M), wheat (W) and field pea (P), from S and M in monoculture to intensified CS with four crops in two years, which included W/S and P/M double crops. We simultaneously measured N-N2O emission, soil nitrate content (N-NO3) and water-filled pore space (WFPS) approximately twice a month during two seasons (2019/20–2020/2021). Low frequencies of elevated values were observed in both N-N2O emissions and N-NO3 levels across all CS. Cumulative N-N2O emissions of CS during two seasons averaged 881 g ha−1, being higher in M-W/S and P/M-W/S, than other CS, not attributable to their configuration nor N inputs. We detected more differences between phases of the same CS than among CS. The contribution of each component of CS was different depending on the CS and their respective phase. We did not find close associations between WFPS or N-NO3 vs N-N2O fluxes. The annualized emission factor obtained at CS level were in the lower bound of the values range usually cited, even slightly lower. The study highlights the importance of including the phase of rotation in studies dealing with N-N2O measurements was reemphasized. Strategies that focus on increasing grain yields and reducing fallow periods remain effective in minimizing emissions per unit of production. These approaches also promote income stability and soil health by facilitating the return of crop residues, contributing to both environmental and economic sustainability.